PENGEMBANGAN E-MODUL BERBASIS DISCOVERY LEARNING PADA PEMBELAJARAN TEMATIK TEMA 6 SUBTEMA 1 HEWAN DI SEKITAR KU SD KELAS II - Nini Sonia; Nila Kesumawati; Nora Sulmilasari (Universitas Negeri Medan, 2021)
This study aims to produce an E-Module based on discovery learning in thematic learning of theme 6 sub-theme 1 for class II SD which is valid and practical and to determine the potential effects of development. This research is included in research and development, referring to the development of ADDIE. The research took place at SDN 199 Palembang. The research subjects were 24 second grade elementary school students. Data collection was carried out by means of a media and language expert validation questionnaire, material expert, mathematics teacher questionnaire, student response questionnaire, and student test result data. The data were analyzed quantitatively and qualitatively. The results showed that the validation of the validators got an average validation score of 88.66% with a valid category. The results of student responses based on trials got an average score of 91.58% in the practical category. The results of the test questions distributed to 24 students contained 21 students who completed and 3 students did not complete, the average student score was 84.50% in the very good category or had a potential effect on student learning outcomes.Keywords: E-Module, ADDIE, Discovery Learning, Thematic Theme 6 Sub-theme 1